Kalıp Ve Kalıp Ayırıcı Yağ Türünün Betonla Sıva Arasındaki Aderansa Etkisi - Eriş, İhsan (Fen Bilimleri Enstitüsü, 2015)
Bu çalışmayla, inşaat sektöründe sıklıkla kullanılan yapı malzemelerinden biri olan betonun; gelişen teknoloji paralelinde farklı açılardan kullanabilirliğin artmasıyla beraber ortaya çıkan yeni problemlerin tespit edilmesi, sonrasında tespit edilen bu problemlere çözüm yollarının geliştirilmesi amaçlanmıştır.Son yıllarda teknolojinin betona kazandırdığı en önemli özellik, betonun renklendirilebilirliği olmuştur. Bu özellik ile birlikte vazgeçilmez malzemelerden biri olan beton, sektörde özellikle mimarların ilgisini çekerek daha cazip hale gelmiştir. Mimari beton, uygulamada düzgün yüzey elde edilebilirliği ölçüsünde yaygınlaşmıştır. Deneysel bir çalışmayla betonda düzgün bir yüzey elde edebilme, dolayısıyla da betonun yüzey düzgünlüğüne birincil derecede etkisi bulunan betonun kalıplanması aşaması üzerinde durulmuştur. Elde edilen düzgün yüzey üzerine yapılacak uygulamalarda aderansın en iyi hangi şartlarda maksimize edilebileceği üzerine kombinezonlar denenmiştir. Bu çalışma uygulamada varolan önemli bir problem için çözüm önerileri geliştirebilmek umuduyla hazırlanmıştır.

Through this study, it is aimed to determine the problems occurred due to the enhanced usability of concrete, which is a major structural material often used in the construction sector, in various aspects in parallel with the constantly improving technology, and to develop further solutions for these determined problems. The most important specificity that the technology provided the concrete with has been coloring. Due to this specificity, the concrete, which is already an indispensable material, has become more attractive in the sector by drawing architects’ attention. Architectural concrete has expanded depending upon its availability for obtaining flat surfaces. Through an experimental study we have focused on obtaining a flat surface in the concrete therefore the casting phase of the concrete which has a prime impact on the concrete’s flatness. Combinations have been tried for the implementations to be carried out on the flat surface to be obtained, through which the adhesion might be optimized under most favorable conditions. This present study has been drawn up in order to be able to offer solutions for a problem already existent in application.
Effect Of The Formwork And The Formwork-separating Oil Type On The Adherence Between The Concrete And The Plaster
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2007
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2007
Keywords: Kalıp; Kalıp Ayırıcı Yağ; Sıva; Aderans; Mimari beton; Formwork; Formwork-Seperating Oil; Plaster; Adherence; Decorative Concrete